Solid electrolyte for solid-state battery and method for producing the same

CN116848066BActive Publication Date: 2026-11-03LG ENERGY SOLUTION LTD +1
View PDF 3 Cites 0 Cited by

Patent Information

Application Number
CN202280007492.X
Authority / Receiving Office
CN · China
Patent Type
Patents(China)
Current Assignee / Owner
Priority Date
2021-04-30
Filing Date
2022-04-29
Publication Date
2026-11-03
Estimated Expiration
2042-04-29

AI Technical Summary

Technical Problem

Existing sulfide-based solid electrolytes have poor water resistance in conventional lithium-ion battery manufacturing environments, easily react with water in the air to produce harmful hydrogen sulfide, leading to safety issues. Furthermore, their compositional spectrum is limited, making them difficult to apply in conventional lithium-ion battery manufacturing processes.

Method used

A solid electrolyte for solid-state batteries containing absorbent materials is used. The sulfide-based solid electrolyte and the absorbent material, such as LiBr, exhibit a binding energy peak observed at 54.2 to 56.1 eV, and the Br3d binding energy exhibits a peak observed at 67.5 to 69.5 eV. The ratio of Br3d peak counts (Br3d peak counts/Li1s peak counts) can be greater than 0.3.

Benefits of technology

It improves the water resistance of solid electrolytes used in solid-state batteries, suppresses H2S generation, and enhances the safety and stability of solid-state batteries, making it suitable for use in dew point environments during conventional lithium-ion battery manufacturing processes.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN116848066B_ABST
    Figure CN116848066B_ABST
Patent Text Reader

Abstract

An object of the present invention is to provide a solid electrolyte for a solid-state battery having improved water resistance. The solid electrolyte for a solid-state battery of the present invention includes a sulfide-based solid electrolyte and an absorbing material containing LiBr, in which, in XPS measurement, the Li1s binding energy shows a peak observed at 54.2 to 56.1 eV, and the Br3d binding energy shows a peak observed at 67.5 to 69.5 eV.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present disclosure relates to a solid electrolyte for solid-state batteries and a method for preparing the same.

[0002] This application claims priority to Japanese Patent Application No. 2021-077607 filed in Japan on April 30, 2021, the disclosure of which is incorporated herein by reference in its entirety. Background Art

[0003] In order to provide batteries with high safety, long service life and high energy density, development of solid-state batteries that use solid electrolytes to replace the liquid electrolytes of lithium ion batteries has been carried out. Among various types of solid electrolytes, sulfide-based solid electrolytes, such as Li 10 GeP2S 12 , have high ionic conductivity close to that of liquid electrolytes and are soft, which is advantageous because tight adhesion to active materials is easily obtained. Therefore, commercialization of solid-state batteries using sulfide-based solid electrolytes is expected.

[0004] However, such sulfide-based solid electrolytes generally have low water resistance, and react with water in air to generate harmful hydrogen sulfide (H2S). Therefore, to obtain solid-state lithium ion batteries using sulfide-based solid electrolytes, an ultra-low dew point environment, for example, a dew point of -80°C, is required. In view of this, H2S may be generated in the conventional lithium ion battery manufacturing environment with a dew point of about -45°C, thus causing safety-related problems.

[0005] Patent Document 1 discloses a composition of a compound having a thio-LISICON germanium-type crystal structure and represented by the chemical formula Li 7-x-2y PS 6-x-y Cl x (wherein 0.8≤x≤1.7, 0<y≤-0.25x+0.5). This compound exhibits water resistance by inhibiting its reactivity with water. However, since the compositional spectrum of sulfide-based solid electrolytes is limited, there is a problem that precise control is required to achieve such a limited composition.

[0006] Accordingly, there is a need to improve the water resistance of sulfide-based solid electrolytes so that the sulfide-based solid electrolytes can be safely prepared even in the dew point environment of conventional lithium ion battery manufacturing processes.

[0007] [References]

[0008] Patent Document 1: Japanese Patent Publication No. 2016-024874 Summary of Invention

[0009] [Technical Problem]

[0010] The present invention aims to solve the problems of related technologies, and therefore aims to provide a solid electrolyte for solid batteries with improved water resistance.

[0011] [Technical Solution]

[0012] In one aspect of this disclosure, a solid electrolyte for solid-state batteries is provided, comprising a sulfide-based solid electrolyte and a LiBr-containing absorbent material, wherein, as determined by X-ray photoelectron spectroscopy (XPS), the binding energy of Li1s shows a peak observed at 54.2 to 56.1 eV, and the binding energy of Br3d shows a peak observed at 67.5 to 69.5 eV.

[0013] According to one implementation, the ratio of the peak count of Br3d to the peak count of Li1s (Br3d peak count / Li1s peak count) can be 0.3 or higher.

[0014] According to another embodiment, sulfide-based solid electrolytes can have a LiGePS-type crystal structure.

[0015] According to another embodiment, XRD measurements show that the ratio of the intensity of the LiBr peak at 2θ = 32.6° to the intensity of the peak of the LiGePS type crystal at 2θ = 29.3° (LiBr peak (2θ = 32.6°) intensity / LiGePS type crystal peak (2θ = 29.3°) intensity) can be 0.02 or higher.

[0016] According to another embodiment, the lattice volume (V) of the solid electrolyte for solid-state batteries and the lattice volume (V0) of the sulfide solid electrolyte satisfy the relationship 0.5 ≤ {(V-V0) / V0} × 100.

[0017] On the other hand, a method for preparing a solid electrolyte for a solid-state battery is provided, comprising the steps of: mixing a sulfide-based solid electrolyte with an absorbent material to obtain a mixture; and heat-treating the mixture, wherein the temperature (T[°C]) of the heat treatment and the melting point (Tm) of the absorbent material are... m [℃]) satisfies T≥T m -60 relationship.

[0018] According to one embodiment, the absorbent material may contain LiBr.

[0019] According to another embodiment, the method may further include a step of adding an absorbent material after the heat treatment step.

[0020] [Beneficial Effects]

[0021] This disclosure provides a solid electrolyte for solid-state batteries with improved water resistance. Because the solid electrolyte for solid-state batteries contains an absorbent material capable of reacting with water to form stable hydrates, the water resistance of the solid electrolyte for solid-state batteries can be improved without limiting the type and composition of sulfide-based solid electrolytes. Attached Figure Description

[0022] Figure 1 The energy spectra of Examples 1-4, Comparative Example 1, and LiBr powder as analyzed by X-ray photoelectron spectroscopy (XPS) are shown.

[0023] Figure 2 The image shows a pattern of Example 1 as determined by X-ray diffraction.

[0024] Figure 3 Enlarged XRD patterns of Examples 1-4 and Comparative Example 1 are shown.

[0025] Figure 4 This is a graph showing the H2S generation of the coarse powder of the respective examples and comparative examples at a dew point of -30°C with varying exposure time.

[0026] Figure 5 This is a graph showing the H2S generation of ≤10μm powder in the respective examples and comparative examples at a dew point of -30°C with varying exposure time.

[0027] Figure 6 This is a graph showing the H2S generation of ≤10μm powder in the examples and comparative examples at a dew point of -45°C with varying exposure time. Detailed Implementation

[0028] Preferred embodiments of the present disclosure will be described in detail below with reference to the accompanying drawings. Before the description, it should be understood that the terminology used in the specification and appended claims should not be construed as limited to its general and dictionary meaning, but should be interpreted based on the principle that the inventors are allowed to appropriately define the terminology for the best interpretation, and based on the meanings and concepts corresponding to the technical aspects of the present disclosure.

[0029] Solid electrolyte for solid-state batteries

[0030] The solid electrolyte for solid-state batteries disclosed herein comprises a sulfide-based solid electrolyte and an absorbent material. Depending on the specific application, the solid electrolyte for solid-state batteries may further comprise additives, such as lithium salts, conductive materials, binder resins, etc.

[0031] <Sulfide Solid Electrolytes>

[0032] There are no particular restrictions on sulfide solid electrolytes, as long as they contain sulfur (S), and any known sulfide solid electrolyte can be used.

[0033] Sulfide solid electrolytes can have crystalline structures. These structures can be NASICON-type, perovskite-type, garnet-type, LiGePS-type, or argyroclase-germanium-sulfurite-type.

[0034] Sulfide solid electrolytes may contain Li, X and S, wherein X may include P, Ge, B, Si, Sn, As, Al, Zr, Ga, V, Nb, Sb, Ti, Cl, F, I, O, N or two or more of them.

[0035] Preferably, the sulfide-based solid electrolyte may have a LiGePS-type crystal structure. The LiGePS-type crystal structure can be incorporating the absorbent material in solid solution form into the crystal structure through heat treatment together with the absorbent material. When the solid electrolyte for solid-state batteries is exposed to water, the absorbent material contained in the solid electrolyte in solid solution form reacts with water to form hydrates, thereby suppressing H2S generation and improving the water resistance of the solid electrolyte for solid-state batteries.

[0036] Sulfide solid electrolytes can be amorphous, vitreous, or glass-ceramic.

[0037] Sulfide solid electrolytes may contain metals belonging to Group 1 or Group 2 of the periodic table, and may include Li-PS type glass or Li-PS type glass-ceramic. Non-limiting examples of sulfide solid electrolytes may include at least one selected from Li₂S-P₂S₅, Li₂S-LiI-P₂S₅, Li₂S-LiI-Li₂O-P₂S₅, Li₂S-LiBr-P₂S₅, Li₂S-Li₂O-P₂S₅, Li₂S-Li₃PO₄-P₂S₅, Li₂S-P₂S₅-P₂O₅, Li₂S-P₂S₅-SiS₂, Li₂S-P₂S₅-SnS, Li₂S-P₂S₅-Al₂S₃, Li₂S-GeS₂, and Li₂S-GeS₂-ZnS.

[0038] <Absorbent Materials>

[0039] The absorbent material can be any known material, as long as it is capable of absorbing water. Preferably, the absorbent material may include lithium bromide (LiBr). When LiBr is included in the solid electrolyte for solid-state batteries, it does not adversely affect the ionic conductivity of the solid electrolyte for solid-state batteries.

[0040] Based on the total weight of the solid electrolyte for solid-state batteries, the amount of absorbent material present can be 0.1 wt% to 10 wt%, preferably 0.5 wt% to 8 wt%, more preferably 1 wt% to 6 wt%, and most preferably 2 wt% to 5 wt%. When the content of absorbent material is within the above range, the generation of H2S can be suppressed and the water resistance of the solid electrolyte for solid-state batteries can be improved. As described below, absorbent material can be further added subsequently to the solid electrolyte for solid-state batteries containing absorbent material.

[0041] The absorbent material can be present on the surface and / or inside the sulfide-based solid electrolyte. When the absorbent material is stably present on the surface and / or in the lattice of the sulfide-based solid electrolyte, it will not adversely affect the ionic conductivity of the solid electrolyte for solid-state batteries, even after reacting with water to form hydrates, and it allows the ionic conductivity of the solid electrolyte for solid-state batteries to be maintained even after the solid electrolyte is exposed to water.

[0042] [XRS Peak]

[0043] When the absorbing material includes LiBr, peaks originating from the binding energies of Li1s and Br3d are detected in the X-ray photoelectron spectroscopy (XPS) of the solid electrolyte for solid-state batteries. In the solid electrolyte for solid-state batteries disclosed herein, LiBr, as the absorbing material, can exist on the surface and / or inside the sulfide-based solid electrolyte. Therefore, there are cases where the binding energies exhibited by the solid electrolyte for solid-state batteries differ from the individual binding energies of Li1s and Br3d detected in the XPS analysis of pure LiBr powder. As shown in Table 2, the Li1s binding energy and Br3d binding energy of pure LiBr powder are 56.19 eV and 68.69 eV, respectively.

[0044] Binding energy

[0045] In the solid electrolyte for solid-state batteries disclosed herein, the binding energy of Li1s exhibits a peak observed at 54.2-56.1 eV, preferably 54.5-55.8 eV, more preferably 54.8-55.5 eV, and most preferably 55.1-55.3 eV. It should be noted that the binding energy of Li1s in the solid electrolyte for solid-state batteries of this disclosure differs from the binding energy of the Li1s peak in pure LiBr powder. It is believed that this difference in the binding energy of the Li1s peak is due to the presence of LiBr as an absorbent material on the surface and / or within the sulfide-based solid electrolyte in the solid electrolyte for solid-state batteries of this disclosure.

[0046] In the solid electrolyte for solid-state batteries disclosed herein, the binding energy of Br3d exhibits a peak observed at 67.5-69.5 eV, preferably 67.8-69.2 eV, more preferably 68.1-68.9 eV, and most preferably 68.4-68.6 eV.

[0047] When the binding energies of Li1s and Br3d are within the aforementioned ranges, the absorbent material LiBr can stably exist on the surface and / or inside the sulfide-based solid electrolyte. In solid electrolytes for solid-state batteries, the stably existing LiBr reacts with water to form hydrates, thereby inhibiting the generation of H2S and improving the water resistance of the solid electrolyte for solid-state batteries.

[0048] <Count ratio>

[0049] The ratio of the peak count of Br3d to the peak count of Li1s (Br3d / Li1s) can be 0.3 or more, preferably 1-10, more preferably 2-8, and most preferably 2.9-6.

[0050] When the count ratio is within the above range, the LiBr contained in the solid electrolyte for solid batteries reacts with water to form hydrates, thereby inhibiting the generation of H2S and improving the water resistance of the solid electrolyte for solid batteries.

[0051] X-ray diffraction (XRD)

[0052] In XRD analysis, the ratio of the peak intensity of LiBr at 2θ = 32.6° to that of LiGePS-type crystals at 2θ = 29.3° (LiBr peak intensity (2θ = 32.6°) / LiGePS-type crystal peak intensity (2θ = 29.3°) can be 0.02 or higher, preferably 0.03-0.15, and more preferably 0.035-0.10. The sulfide-based solid electrolyte of LiGePS-type crystals can be Li... 10 SnP2S 12 The LiBr peak at 2θ = 32.6° can be a peak corresponding to the (2,0,0) plane of LiBr, and the peak of the LiGePS type crystal at 2θ = 29.3° can be a peak corresponding to the (2,0,3) plane of the LiGePS type crystal.

[0053] When the peak intensity ratio is within the above range, LiBr contained in the solid electrolyte for solid-state batteries can exist stably in crystalline form and react with water to form hydrates, thereby inhibiting the generation of H2S and improving the water resistance of the solid electrolyte for solid-state batteries.

[0054] The 2θ value in XRD can vary with measurement errors, etc. According to this disclosure, a specific value of 2θ can be interpreted as a range of [a specific value of 2θ ± 0.1°]. For example, "the intensity of the LiBr peak present at 2θ = 32.6°" can be interpreted as the intensity of the LiBr peak detected at 32.5-32.7°.

[0055] [Lattice volume]

[0056] The lattice volume of solid electrolytes used in solid-state batteries can be increased by introducing absorbent materials into the lattice of sulfide-based solid electrolytes.

[0057] The relationship between the lattice volume (V) of the solid electrolyte for the solid-state battery and the lattice volume (V0) of the sulfide solid electrolyte satisfies 0.5 ≤ {(V-V0) / V0} × 100, preferably 0.65 ≤ {(V-V0) / V0} × 100, more preferably 1.0 ≤ {(V-V0) / V0} × 100, and most preferably 1.3 ≤ {(V-V0) / V0} × 100. Here, {(V-V0) / V0} × 100 can be 5.0 or less, 2.5 or less, or 2.0 or less.

[0058] When the relationship falls within the range defined above, LiBr contained in the solid electrolyte for solid-state batteries can react with water to form hydrates, thereby inhibiting the generation of H2S and improving the water resistance of the solid electrolyte for solid-state batteries.

[0059] [Heat treatment temperature]

[0060] Solid electrolytes for solid-state batteries are obtained by a method comprising the following steps: mixing a sulfide-based solid electrolyte with an absorbent material to obtain a mixture; and heat-treating the mixture, wherein the heat treatment temperature (T [°C]) and the melting point (T [°C]) of the absorbent material are... m [℃]) satisfies T≥T m The relationship is -60. The heat treatment temperature can be the temperature at which the components contained in the solid electrolyte for solid-state batteries do not undergo thermal decomposition.

[0061] Because the heat treatment temperature is close to the melting point of the absorbent material, interdiffusion is accelerated even in the case of a solid absorbent material, thus the absorbent material exists on the surface and / or inside the sulfide-based solid electrolyte. When the heat treatment temperature is higher than the melting point of the absorbent material, the absorbent material exists in a liquid state and has fluidity, thus easily accommodated in the crystal lattice of the sulfide-based solid electrolyte as a solid solution. Therefore, the crystal volume of the solid electrolyte for solid-state batteries of this disclosure becomes larger than the crystal volume of the sulfide-based solid electrolyte without the absorbent material in a solid solution state.

[0062] Heat treatment temperature (T [°C]) and melting point of the absorbent material (T m The relationship between [℃] and [℃] satisfies T≥T m -60, preferred T m +60≥T≥T m -60, more preferably T m +50≥T≥T m -50.

[0063] The heat treatment temperature (T [°C]) can satisfy T≥490°C, preferably 610°C≥T≥490°C, and more preferably 600°C≥T≥550°C.

[0064] When the heat treatment temperature (T [°C]) and the melting point of the absorbent material (T) m When the above-defined range is met (°C), the mixing of the sulfide-based solid electrolyte and the absorbent material is accelerated, thus the absorbent material exists on the surface and / or inside the sulfide-based solid electrolyte. Therefore, the absorbent material contained in the solid electrolyte for solid-state batteries can react with water to form hydrates, thereby inhibiting the generation of H2S and improving the water resistance of the solid electrolyte for solid-state batteries.

[0065] The steps of mixing the sulfide-based solid electrolyte with the absorbent material to obtain the mixture and the heat treatment of the mixture can be carried out under an inert atmosphere. In this document, "inert atmosphere" refers to an atmosphere filled with a known inert gas (e.g., argon or nitrogen).

[0066] The step of mixing a sulfide-based solid electrolyte with an absorbent material to obtain a mixture may include the step of forming the sulfide-based solid electrolyte from raw materials. The raw materials for the sulfide-based solid electrolyte may be any known material used to form the sulfide-based solid electrolyte.

[0067] [Addition of absorbent material]

[0068] After mixing and heat-treating the mixture obtained by mixing sulfide-based solid electrolytes with absorbent materials, a further step can be taken to add absorbent materials to the solid electrolyte for solid-state batteries.

[0069] Based on the total weight of the solid electrolyte for solid-state batteries, the absorbent material can be added in an amount of 0.1 wt% to 10 wt%, preferably 0.5 wt% to 8 wt%, more preferably 1 wt% to 6 wt%, and most preferably 2 wt% to 5 wt%. In other words, based on the total weight of the solid electrolyte for solid-state batteries, the sum of the absorbent material contained in the solid electrolyte for solid-state batteries and the subsequently added absorbent material can be 0.2 wt% to 20 wt%, preferably 1 wt% to 16 wt%, more preferably 2 wt% to 12 wt%, and most preferably 4 wt% to 10 wt%.

[0070] Adding absorbent material after heat treatment of the solid electrolyte for solid-state batteries can increase the amount of absorbent material contained in the solid electrolyte, thereby suppressing the generation of H2S and improving the water resistance of the solid electrolyte for solid-state batteries.

[0071] Solid-state batteries

[0072] The solid-state battery electrolyte disclosed herein can be used in solid-state batteries comprising a positive electrode, a negative electrode, and a solid electrolyte membrane. The solid electrolyte can be used as a component of the solid electrolyte membrane. The solid electrolyte can be used with active materials in the respective electrode active material layers of the positive and negative electrodes. The average particle size of the solid-state battery electrolyte can be controlled according to the specific application.

[0073] Solid electrolyte membranes

[0074] According to this disclosure, the solid electrolyte membrane can have a thickness of about 50 μm or less, preferably about 15-50 μm. Considering the ionic conductivity, physical strength, energy density, etc., of the applicable battery, the solid electrolyte membrane can have a suitable thickness. For example, in terms of ionic conductivity or energy density, the thickness can be 10 μm or more, 20 μm or more, or 30 μm or more. Meanwhile, in terms of physical strength, the thickness can be 50 μm or less, 45 μm or less, or 40 μm or less. Furthermore, while the solid electrolyte membrane has the thickness range defined above, its tensile strength can be about 100-2000 kgf / cm². 2 Furthermore, the porosity of the solid electrolyte membrane can be less than 15% by volume or less than about 10% by volume. Therefore, even if the solid electrolyte membrane of this disclosure is a thin film, it can still have high mechanical strength.

[0075] Positive and negative electrodes

[0076] According to this disclosure, the positive and negative electrodes each include a current collector and an electrode active material layer formed on at least one surface of the current collector, wherein the electrode active material layer includes a plurality of electrode active material particles and a solid electrolyte. If desired, the electrodes may further include at least one of a conductive material and a binder resin. Additionally, the electrodes may include various additives to supplement or improve the physical / chemical properties of the electrodes.

[0077] According to this disclosure, the negative electrode active material can be any material, as long as it can be used as a negative electrode active material for lithium-ion secondary batteries. Specific examples of negative electrode active materials include any of the following: carbon, such as non-graphitized carbon or graphite-based carbon; metal composite oxides, such as Li... x Fe2O3 (0≤x≤1), Li x WO2(0≤x≤1), Sn x Me 1-x Me' y O z(Me: Mn, Fe, Pb, Ge; Me': Al, B, P, Si, an element of Group 1, 2 or 3 of the periodic table, halogen; 0<x≤1; 1≤y≤3; 1≤z≤8); lithium metal; lithium alloy; silicon-based alloy; indium metal; indium alloy; tin-based alloy; metal oxides, such as SnO, SnO₂, PbO, PbO₂, Pb₂O₃, Pb₃O₄, Sb₂O₃, Sb₂O₄, Sb₂O₅, GeO, GeO₂, Bi₂O₃, Bi₂O₄ and Bi₂O₅; conductive polymers, such as polyacetylene; Li-Co-Ni based materials; and titanium oxide; or a mixture of two or more thereof. According to an embodiment of the present disclosure, the negative electrode active material may include a carbonaceous material and / or Si.

[0078] In the case of a positive electrode, the electrode active material may be any material without particular limitation, as long as it can be used as the positive electrode active material of a lithium ion secondary battery. For example, the positive electrode active material may include any one selected from the following: layered compounds, such as lithium cobalt oxide (LiCoO₂) and lithium nickel oxide (LiNiO₂), or these compounds substituted with one or more transition metals; lithium manganese oxides, such as those represented by the chemical formula Li 1+x Mn 2-x O₄ (wherein x is 0-0.33), LiMnO₃, LiMn₂O₃ and LiMnO₂; lithium copper oxide (Li₂CuO₂); vanadium oxides, such as LiV₃O₈, LiV₃O₄, V₂O₅ or Cu₂V₂O₇; nickel-site type lithium nickel oxides represented by the chemical formula LiNi 1-x M x O₂ (wherein M is Co, Mn, Al, Cu, Fe, Mg, B or Ga, and x is 0.01-0.3); lithium manganese composite oxides represented by the chemical formula LiMn 2-x M x O₂ (wherein M is Co, Ni, Fe, Cr, Zn or Ta, and x is 0.01-0.1) or Li₂Mn₃MO₈ (wherein M is Fe, Co, Ni, Cu or Zn); lithium manganese composite oxides with a spinel structure represented by the formula LiNi x Mn 2-x O₄; NCM-based composite oxides represented by the chemical formula Li(Ni a Co b Mn c )O₂ (wherein a, b and c each independently represent the atomic fraction of the element, 0<a<1, 0<b<1, 0<c<1, and a+b+c=1); LiMn₂O₄ in which Li is partially substituted with an alkaline earth metal ion; disulfide compounds; Fe₂(MoO₄)₃; and the like. However, the scope of the present disclosure is not limited thereto.

[0079] According to this disclosure, the current collector can be selected from current collectors that are conductive and known in the field of secondary batteries, such as metal plates, depending on the polarity of the electrode.

[0080] According to this disclosure, conductive materials are typically added in an amount of 1-30% by weight, based on the total weight of the mixture containing electrode active materials. The conductive materials are not particularly limited, provided they do not cause chemical changes in the corresponding battery and are conductive. For example, conductive materials include any of the following: graphite, such as natural or artificial graphite; carbon black, such as acetylene black, Ketjen black, channel black, furnace black, lamp black, or thermally cracked carbon black; conductive fibers, such as carbon fibers or metal fibers; fluorinated carbon; metal powders, such as aluminum or nickel powder; conductive whiskers, such as zinc oxide or potassium titanate; conductive metal oxides, such as titanium oxide; and conductive materials such as polyphenylene derivatives, or mixtures of two or more of these.

[0081] There are no particular limitations on the adhesive resin, as long as it is a component that facilitates the adhesion between the active material and the conductive material, as well as the adhesion between the active material and the current collector. Specific examples of adhesive resins include: polyvinylidene fluoride, polyvinyl alcohol, carboxymethyl cellulose (CMC), starch, hydroxypropyl cellulose, regenerated cellulose, polyvinylpyrrolidone, polytetrafluoroethylene, polyethylene, polypropylene, ethylene-propylene-diene monomer terpolymer (EPDM), sulfonated EPDM, styrene-butadiene rubber, fluororubber, and various copolymers thereof. Typically, based on 100% by weight of the electrode active material layer, the adhesive resin can be used in amounts of 1-30% by weight or 1-10% by weight.

[0082] According to this disclosure, the electrode active material layer may further include at least one additive, such as an oxidation stabilizer, a reduction stabilizer, a flame retardant, a heat stabilizer, an antifogging agent, etc.

[0083] In another aspect of this disclosure, a battery module is provided, comprising the battery as a unit cell; a battery pack comprising the battery module; and a device comprising the battery pack as a power source. Specific examples of this device may include, but are not limited to: power tools driven by an electric motor; electric vehicles, including electric vehicles (EVs), hybrid electric vehicles (HEVs), plug-in hybrid electric vehicles (PHEVs), etc.; electric two-wheelers, including electric bicycles (E-bicycles) and electric scooters (E-scooters); electric golf carts; energy storage systems; and so on.

[0084] Example

[0085] The embodiments will be described more fully below to facilitate a better understanding of the invention. However, the following embodiments are for illustrative purposes only, and the scope of this disclosure is not limited thereto.

[0086] (Example 1)

[0087] First, lithium sulfide (Li₂S, available from Mitsuwa Chemical), phosphorus pentasulfide (P₂S₅, available from Aldrich), tin sulfide (SnS₂, available from Japan Pure Chemical), and lithium bromide (LiBr, available from Aldrich) were used as components of the solid electrolyte for solid-state batteries. The components were weighed and mixed in a mortar and pestle under an argon atmosphere in a glove box, so that the final solid electrolyte for solid-state batteries had a composition of Li₂S₅. 3.36 Sn 0.335 P 0.64 S 3.9 Br 0.1 In this manner, a mixed powder is obtained. The resulting mixed powder is introduced into a ZrO2 jar along with ZrO2 balls to provide a sealed jar. The sealed jar is installed in a planetary ball mill and ball-milled at 380 rpm for 20 hours, then the jar is opened in a glove box to recover the powder. The resulting powder is placed on an alumina boat and installed in an electric furnace, then calcined at a firing temperature of 550°C for 8 hours with argon gas flowing through it. The calcined powder is then pulverized in a mortar for 10 minutes to obtain a solid electrolyte for solid-state batteries.

[0088] (Example 2)

[0089] A solid electrolyte for solid-state batteries was obtained in the same manner as in Example 1, except that the firing temperature was 600°C.

[0090] (Example 3)

[0091] A solid electrolyte for solid-state batteries was obtained in the same manner as in Example 1, except that the composition of the solid electrolyte was Li. 3.40 Sn 0.375 P 0.60 S 3.9 Br 0.1 .

[0092] (Example 4)

[0093] A solid electrolyte for solid-state batteries was obtained in the same manner as in Example 1, except that the firing temperature was 500°C.

[0094] (Comparative Example 1)

[0095] A solid electrolyte for solid-state batteries was obtained in the same manner as in Example 1, except that lithium bromide was not used and the composition of the solid electrolyte was Li. 3.33 Sn 0.33 P 0.67 S4.

[0096] (Comparative Example 2)

[0097] A solid electrolyte for solid-state batteries was obtained in the same manner as in Example 1, except that lithium bromide was not used, and germanium disulfide (GeS2, available from Japan Pure Chemical) was used instead of tin sulfide, and the composition of the solid electrolyte was Li. 3.45 Sn 0.45 P 0.55 S4.

[0098] (Example 5)

[0099] LiBr powder, at a weight of 4% by weight based on the total weight of the solid electrolyte for solid batteries, was added to the solid electrolyte for solid batteries obtained in Example 1, and the components were mixed in a mortar for 10 minutes. In this way, a solid electrolyte for solid batteries with added LiBr was obtained.

[0100] (Example 6)

[0101] LiBr powder, at a weight of 4% based on the total weight of the solid electrolyte for solid batteries, was added to the solid electrolyte for solid batteries obtained in Comparative Example 2, and the components were mixed in a mortar for 10 minutes. In this way, a solid electrolyte for solid batteries with added LiBr was obtained.

[0102] [evaluate]

[0103] The following is an evaluation of the solid electrolyte used in each solid-state battery.

[0104] [XPS Analysis]

[0105] X-ray photoelectron spectroscopy (XPS)

[0106] Under ultra-high vacuum, soft X-rays are irradiated onto the surface of a sample, and photoelectrons emitted from the surface are detected using an analyzer. If the distance the photoelectrons can travel into the material (mean free path) is determined to be a few nanometers, the detection depth of this analysis is also a few nanometers. Elemental information about the surface is obtained from the binding energies of the electrons confined within the material, and information about valence or binding states is obtained from the energy transfer of each peak. The elemental ratio (composition) can be quantitatively estimated from the peak area ratio.

[0107] -sample

[0108] Powdered solid electrolytes for each solid-state battery were immobilized in indium foil as samples. The powders were sampled and transferred to the apparatus under an argon atmosphere.

[0109] -Analysis conditions

[0110] Device: Quantera SXM (Ulvac-PHI)

[0111] Excitation X-rays: Monochromatic AlK1,2 rays (1486.6 eV)

[0112] X-ray penetration: 200μm

[0113] Photoelectronic detection angle: 45° (slope of the detector relative to the sample surface)

[0114] -Data Processing

[0115] Smoothing: 9-point smoothing

[0116] For horizontal axis correction, the C1s main peak (CHx, CC) was set to 284.6 eV.

[0117] [XRD Analysis]

[0118] Each solid-state battery was introduced into a sealed holder in a glove box under argon atmosphere using a solid electrolyte, and the lattice constant and lattice volume were calculated from the diffraction pattern by X-ray diffraction (XRD).

[0119] [Generation of H2S]

[0120] In a glove box with a dew point set at -30°C, each type of solid-state battery electrolyte (coarse powder) or solid-state battery electrolyte with an average particle size of less than 10 μm was sealed in a plastic box along with an H2S gas concentration analyzer. The H2S level (ppm) was then measured over time. The H2S yield (mL / g) per gram of solid-state battery electrolyte was calculated from the obtained H2S level (ppm), the weight of the solid electrolyte, and the volume of the plastic box.

[0121] Each type of solid-state battery electrolyte was pulverized in a mortar for 1 hour and then sieved to obtain solid-state battery electrolytes with an average particle size of less than 10 μm. The average particle size of the solid-state battery electrolyte can be determined and evaluated using any known technique (e.g., scanning electron microscopy).

[0122] [Determination of ionic conductivity]

[0123] Each type of solid electrolyte for solid-state batteries is weighed to a predetermined amount. The wafer forming jig (lower jig) is assembled with a Macor tube, and the weighed solid electrolyte is then introduced into the Macor tube. Next, the wafer forming jig (upper jig) is attached to it, and pressing is performed using a uniaxial press at 5 MPa. Afterward, a predetermined amount of gold powder is applied to both surfaces of the wafer, and pressing is performed using a uniaxial press at 7.5 MPa.

[0124] Install the Macor tube unit onto the battery clamp unit and apply pressure to 5.0N using a torque wrench. . m is used to obtain the ionic conductivity testing unit.

[0125] Connect the test unit to an impedance analyzer and measure the resistance of the solid electrolyte flakes to calculate the ionic conductivity.

[0126] Weigh each solid electrolyte for solid-state batteries in a predetermined amount and expose it to air in a glove box with a dew point of -45°C for 2 hours to determine its ionic conductivity.

[0127] Solid-state battery manufacturing

[0128] <Positive Electrode Mixture>

[0129] NCM-based positive electrode active material and solid electrolyte powder for solid batteries with an average particle size of less than 10 μm were weighed at a weight ratio of 70:30. Then, 5... 2mm agate balls were added to the mixture and ball-milled at 140 rpm for 20 minutes to obtain the positive electrode mixture.

[0130] <Solid Electrolyte Flakes>

[0131] The obtained solid-state battery was weighed with 80 mg of solid electrolyte, installed in a molding fixture, and pressurized at 6 MPa for 1 minute to obtain solid electrolyte granules.

[0132] <Positive Electrode Layer>

[0133] First, 10 mg of positive electrode mixture is provided on one side of the solid electrolyte granules. Then, the positive electrode side pin of the forming jig is gently pressed onto the positive electrode mixture to flatten the solid electrolyte granules, thereby forming the positive electrode layer.

[0134] Solid-state batteries

[0135] An aluminum mesh and an aluminum plate are sequentially placed on the positive electrode layer and pressurized at 30 MPa for 1 minute. Then, indium foil, lithium foil, and a copper mesh are sequentially provided on the surface of the solid electrolyte pellet opposite to the positive electrode side, and pressurized at 12 MPa for 3 seconds. Afterward, positive and negative electrode pins are connected to the molded product to obtain a Macor tube cell. The Macor tube unit is installed in the battery cell, and a 20 N pressure is applied. . A torque of m is used to obtain a solid-state battery. This solid-state battery has a structure of positive electrode side pin / aluminum plate / aluminum mesh / positive electrode layer / solid electrolyte / indium foil / lithium foil / copper mesh / negative electrode side pin. The aluminum plate and aluminum mesh are used as positive electrode current collectors, the indium foil and lithium foil are used as negative electrode active materials, and the copper mesh is used as the negative electrode current collector.

[0136] In addition, solid-state batteries were exposed to a solid electrolyte at a dew point of -45°C for 2 hours to obtain solid electrolyte pellets. Solid-state batteries were then obtained using these solid electrolyte pellets in the same manner as described above.

[0137] [Charging / Discharging Test]

[0138] Charge / discharge tests were conducted using solid-state batteries. The voltage range was 3.6–1.9V. Charging conditions were constant current (CC) (0.05C)–constant voltage (CV) (0.01C), and discharging conditions were CC (0.05C). Initial charge capacity, initial discharge capacity, and initial efficiency were obtained from the charge / discharge curves.

[0139] (Evaluation Results)

[0140] [XPS Analysis]

[0141] The results of the XPS analysis are shown in Tables 1 and 2, and... Figure 1 middle. Figure 1 XPS spectra of Examples 1-4, Comparative Example 1, and LiBr powder are shown. Figure 1 As shown in Table 1, the solid electrolytes for solid-state batteries in Examples 1-4, each containing LiBr as the absorbent material, exhibit two peaks: Li1s and Br3d. Meanwhile, in the case of the solid electrolyte for solid-state batteries in Comparative Example 1, which does not contain LiBr, there is essentially no Br3d peak. It is believed that the Li1s peak observed in Comparative Example 1 originates from Li contained in the sulfide-based solid electrolyte.

[0142] [Table 1]

[0143]

[0144] Table 2 shows the Br3d peak count, Br3d peak binding energy, Li1s peak count, Li1s peak binding energy, and count ratio (Br3d / Li1s).

[0145] [Table 2]

[0146] Peaks and binding energies in XPS spectra

[0147]

[0148] As shown in Table 2, in Examples 1-4, the binding energy of the Li1s peak in Example 1 was 55.25 eV, the binding energy of the Li1s peak in Example 2 was 55.26 eV, the binding energy of the Li1s peak in Example 3 was 55.25 eV, the binding energy of the Li1s peak in Example 4 was 55.12 eV, and the binding energy of the Li1s peak in Comparative Example 1 was 55.25 eV. Furthermore, the binding energy of the Br3d peak in Example 1 was 68.55 eV, the binding energy of the Br3d peak in Example 2 was 68.56 eV, the binding energy of the Br3d peak in Example 3 was 68.55 eV, the binding energy of the Br3d peak in Example 4 was 68.42 eV, and the binding energy of the Br3d peak in Comparative Example 1 was 68.55 eV. Meanwhile, in the case of pure LiBr powder, the binding energy of the Li1s peak is 56.19 eV, and the binding energy of the Br3d peak is 68.69 eV.

[0149] Compared to the binding energy of the Li1s peak of LiBr powder, the binding energy of the Li1s peak of LiBr contained in the solid electrolyte for solid-state batteries of this disclosure is reduced by 0.93 to 1.07 eV. Compared to the binding energy of the Br3d peak of LiBr powder, the binding energy of the Br3d peak of LiBr contained in the solid electrolyte for solid-state batteries of this disclosure is reduced by 0.13 to 0.27 eV. These results are believed to be because the presence of LiBr on the surface and / or inside the sulfide-based solid electrolyte of this disclosure causes the binding energies of the Li1s and Br3d peaks to differ from the binding energies of LiBr as a simple substance.

[0150] As shown in Table 2, the count ratio (Br3d peak / Li1s peak) of Example 1 was 3.224, that of Example 2 was 2.923, that of Example 3 was 3.523, that of Example 4 was 3.348, and that of Comparative Example 1 was 0.205. It can be seen that Examples 1-4, which contain LiBr in their solid electrolyte for solid-state batteries, exhibited higher count ratios, while Comparative Example 1, which does not contain LiBr in its solid electrolyte for solid-state batteries, showed virtually no Br3d peak as detected by XPS and provided a lower count ratio.

[0151] [XRD Analysis]

[0152] The results of the XRD analysis are shown in Tables 1, 3, and 4, and... Figure 2 and 3 middle.

[0153] <Crystal phase>

[0154] Table 1 shows the evaluation results of the crystal phases identified from the XRD patterns obtained by XRD analysis.

[0155] Figure 2The XRD pattern of Example 1 is shown (10°≤2θ≤35°). It can be seen that Li, which contains a peak at approximately 29.3° as the main phase, was obtained. 10 SnP2S 12 (LiGePS type crystal) Sulfide solid electrolyte for solid-state batteries.

[0156] Figure 3 Enlarged XRD patterns (30° ≤ 2θ ≤ 35°) of Examples 1-4 and Comparative Example 1 are shown. In Examples 2 and 3, a LiBr crystalline phase with a peak at approximately 32.6° was detected. Although not shown, a LiBr crystalline phase with a peak at approximately 32.6° was detected in Examples 5 and 6, which contained added LiBr. Conversely, no LiBr crystalline phase with a peak at approximately 32.6° was detected in Examples 1 and 4 and Comparative Example 1. Example 1 involved calcination at 550°C in the same manner as Example 3, but no LiBr crystalline phase was detected. This is believed to be because Examples 1 and 3 have different compositional compositions. In Examples 1 and 4, Li1s and Br3d peaks were detected from XPS analysis results, suggesting that LiBr exists in the lattice as a solid solution or as an amorphous form within Li. 10 SnP2S 12 The surface and / or interior.

[0157] Table 3 shows the half-peak widths (WHMs) of the LiBr peaks obtained from the XRD patterns. Examples 2 and 3 show WHMs of 0.16° and 0.21°, respectively.

[0158] Table 3 also shows the LiBr peak (32.6°) intensity / Li 10 SnP2S 12 The ratio of peak (29.3°) intensity is based on Li at approximately 29.3° after removing the background. 10 SnP2S 12 The maximum peak intensity of (LiGePS type crystal) (see) Figure 2 The peak intensity of the LiBr phase at approximately 32.6° is shown in Examples 2 and 3. Examples 2 and 3 respectively show the LiBr peak intensity (32.6°) / Li 10 SnP2S 12 The ratio of peak (29.3°) intensity was 0.079 and 0.039.

[0159] [Table 3]

[0160] Full width at half maximum (FWHM) of LiBr peak and LiBr / Li in Examples 1-4 and Comparative Example 1 10 SnP2S 12 ( LiGePS (type of crystal) Peak intensity ratio

[0161] <Lattice constant and lattice volume>

[0162] Table 4 shows the lattice constants and lattice volumes calculated from the XRD patterns. The lattice volume of Example 1 is...

[0163] The lattice volume of Example 2 is The lattice volume of Example 3 is The lattice volume of Example 4 is The lattice volume of Comparative Example 1 is Based on the fact that the solid electrolyte used in solid-state batteries is composed of Li 3.33 Sn 0.33 P 0.67 The lattice volume of Comparative Example 1 (S4) and the lattice volumes of Examples 1-4 are 1.67%, 1.37%, 0.67%, and 0.52% larger than that of Comparative Example 1, respectively. This is believed to be because, through firing (heat treatment) at a temperature close to the melting point of LiBr (552°C), LiBr is contained in the LiBr in the form of a solid solution. 10 SnP2S 12 In the main phase, the lattice volume of the solid electrolyte used in solid-state batteries increases.

[0164] [Table 4]

[0165]

[0166] [Generation of H2S]

[0167] The H2S generation results are shown in Table 1 and Figure 4-6 middle. Figure 4The variation of H2S generated from solid electrolyte (coarse powder) for solid-state batteries over exposure time is shown for 0-60 minutes at a dew point of -30°C. Table 1 shows the H2S generation when the solid electrolyte is exposed at a dew point of -30°C for 60 minutes. The H2S yield was 0.14 mL / g in Example 1, 0.12 mL / g in Example 2, 0.12 mL / g in Example 3, 0.18 mL / g in Example 4, 0.08 mL / g in Example 5, 0.28 mL / g in Example 6, 0.33 mL / g in Comparative Example 1, and 0.40 mL / g in Comparative Example 2. Compared to Comparative Examples 1 and 2, which only calcined sulfide-based solid electrolytes, Examples 1-4, which calcined both sulfide-based solid electrolytes and absorbent materials, were able to suppress H2S generation. It can be seen that when exposed to water similar to that used in conventional lithium-ion battery manufacturing processes, the solid electrolyte for solid-state batteries disclosed herein can suppress the generation of H2S.

[0168] It is believed that LiBr exists as an absorbent material in Li 10 SnP2S 12 On the surface and / or inside, LiBr forms hydrates with water to inhibit the generation of H2S.

[0169] Furthermore, in Example 5 (where LiBr was subsequently added to the solid electrolyte for a solid-state battery of Example 1), H2S generation was suppressed to a higher degree compared to Example 1. In Example 6 (where LiBr was subsequently added to the solid electrolyte for a solid-state battery of Comparative Example 2), H2S generation was suppressed to a higher degree compared to Comparative Example 2. When the absorbent material is mixed with the solid electrolyte for a solid-state battery, the effect of suppressing H2S generation exists even if the absorbent material is not contained in the lattice of the sulfide-based solid electrolyte in the form of a solid solution.

[0170] Figure 5 The variation of H2S generated from a solid electrolyte for solid-state batteries with an average particle size of less than 10 μm over exposure time is shown when the solid electrolyte for solid-state batteries is exposed at a dew point of -30°C for 0-60 minutes. When the solid electrolyte for solid-state batteries is exposed at a dew point of -30°C for 0-60 minutes, the H2S yield is 0.22 mL / g in Example 1, 0.16 mL / g in Example 2, 0.35 mL / g in Example 3, 0.36 mL / g in Example 4, 0.22 mL / g in Example 5, and 0.87 mL / g in Comparative Example 2.

[0171] Figure 6The variation of H2S generated from a solid electrolyte for solid-state batteries with an average particle size of less than 10 μm at a dew point of -45°C for 0-60 minutes is shown. When the solid electrolyte for solid-state batteries was exposed at a dew point of -45°C for 0-60 minutes, the H2S yield was 0.12 mL / g in Example 1, 0.05 mL / g in Example 2, 0.07 mL / g in Example 3, 0.15 mL / g in Example 4, and 0.25 mL / g in Comparative Example 2.

[0172] The solid electrolyte for solid-state batteries disclosed herein can suppress H2S generation even when it is pulverized into fine powder below 10 μm.

[0173] [Ionic conductivity and its retention rate]

[0174] The results of ionic conductivity and its retention rate are shown in Table 5. Table 5 shows the initial ionic conductivity, the ionic conductivity after exposure to a dew point of -45°C for 2 hours, and the ionic conductivity retention rate of solid electrolyte sheets formed using solid electrolytes for solid-state batteries. The ionic conductivity retention rate was calculated using the mathematical formula (ionic conductivity after exposure to a dew point of -45°C for 2 hours) / (initial ionic conductivity) × 100 (%). The ionic conductivity retention rate was 95.2% for Example 1, 97.7% for Example 2, 90.6% for Example 3, 83.2% for Example 4, 97.2% for Example 5, 95.8% for Example 6, 84.2% for Comparative Example 1, and 89.5% for Comparative Example 2. Compared to Comparative Examples 1 and 2, Examples 1-3, 5, and 6 exhibit higher ionic conductivity retention. It can be seen that the solid electrolyte for solid-state batteries containing absorbent materials of this disclosure maintains a high level of ionic conductivity even when exposed to water.

[0175] [Table 5]

[0176]

[0177] [Charging / Discharging Test]

[0178] The charge / discharge test results are shown in Table 6. Table 6 shows the initial charge capacity, initial discharge capacity, and initial efficiency of the solid-state batteries of Examples 1 and 2. Example 1 shows an initial charge capacity of 177.6 mAh / g, an initial discharge capacity of 166.1 mAh / g, and an initial efficiency of 93.5%. Example 2 shows an initial charge capacity of 182.0 mAh / g, an initial discharge capacity of 166.0 mAh / g, and an initial efficiency of 91.2%.

[0179] Furthermore, in the case of a solid-state battery using a solid electrolyte obtained by exposing each solid electrolyte to a dew point of -45°C for 2 hours, Example 1 showed an initial charge capacity of 180.9 mAh / g, an initial discharge capacity of 167.9 mAh / g, and an initial efficiency of 92.8%. Example 2 showed an initial charge capacity of 177.9 mAh / g, an initial discharge capacity of 165.8 mAh / g, and an initial efficiency of 93.2%.

[0180] [Table 6]

[0181] Initial charge capacity, initial discharge capacity, and initial efficiency of solid-state batteries

[0182]

[0183] Solid-state batteries using the solid electrolyte of this disclosure can be charged / discharged without problems and exhibit excellent battery characteristics. Even after being exposed to a dew point of -45°C for 2 hours, the solid-state battery maintains high initial charge capacity, initial discharge capacity, and initial efficiency.

[0184] This disclosure has been described in detail. However, it should be understood that although preferred embodiments of this disclosure have been pointed out, the detailed description and specific examples are given by way of illustration only, as various changes and modifications within the scope of this disclosure will become apparent to those skilled in the art based on the detailed description.

Claims

1. A solid electrolyte for solid-state batteries, comprising: Sulfide solid electrolytes; and LiBr-containing absorbent materials, in, X-ray photoelectron spectroscopy (XPS) determined that the binding energy of Li1s showed a peak observed at 54.2 to 56.1 eV, and the binding energy of Br3d showed a peak observed at 67.5 to 69.5 eV. The sulfide-based solid electrolyte has a LiGePS-type crystal structure. The sulfide-based solid electrolyte contains Li, P, Sn, and S; Wherein, the lattice volume V of the solid electrolyte for the solid-state battery and the lattice volume V0 of the sulfide solid electrolyte satisfy the relationship 0.5 ≤ {(V-V0) / V0} × 100.

2. The solid electrolyte for solid-state batteries as described in claim 1, wherein, The ratio of Br3d peak count to Li1s peak count, "Br3d peak count / Li1s peak count", is greater than 0.

3.

3. The solid electrolyte for solid-state batteries as described in claim 1 or 2, wherein, The amount of the absorbent material is from 0.1% to 10% by weight, based on the total weight of the solid electrolyte for the solid battery.

4. The solid electrolyte for a solid-state battery as described in claim 1 or 2, wherein, XRD analysis showed that the ratio of the intensity of the LiBr peak at 2θ=32.6° to the intensity of the LiGePS-type crystal peak at 2θ=29.3° (LiBr peak intensity / LiGePS-type crystal peak intensity) was greater than 0.

02.

5. The solid electrolyte for a solid-state battery as described in claim 1 or 2, wherein, The lattice volume V of the solid electrolyte for the solid-state battery and the lattice volume V0 of the sulfide solid electrolyte satisfy the relationship 1.0 ≤ {(V-V0) / V0} × 100.

6. A method for preparing a solid electrolyte for a solid-state battery according to any one of claims 1 to 5, comprising the following steps: A sulfide solid electrolyte containing Li, P, Sn, and S is mixed with an absorbent material containing LiBr to obtain a mixture; and Heat treatment of the mixture, Wherein, the heat treatment temperature T °C and the melting point T of the absorbent material are... m °C satisfies T≥T m -60 relationship.

7. The method for preparing a solid electrolyte for a solid-state battery as described in claim 6, further comprising the step of adding an absorbent material after the heat treatment step.

Citation Information

Patent Citations

  • Sulfide-based solid electrolyte for lithium ion batteries

    JP2016024874A

  • Spark plug

    JP2021077607A

  • Sulfide solid electrolyte material, battery, and method for producing sulfide solid electrolyte material

    CN105304937A